2021
DOI: 10.1016/j.seizure.2020.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Does glucose influence multidien cycles of interictal and/or ictal activities?

Abstract: There are multidien patterns of seizure occurrence. Predicting seizure risk may be easier with biomarker correlates to multidien patterns. We hypothesize multiday hyper or hypoglycemia contributes to seizure risk. Methods: In a type I diabetic (T1D) with focal onset epilepsy with continuous glucose monitoring (CGM) and responsive neurostimulation (RNS) devices, we studied multiday interictal activities (IEA), seizures, and glucose. Hourly CGM data was matched to hourly RNS captures of interictal and ictal acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…1H, Paired t-test: all P < 0.05). As there have been studies associating interictal epileptiform discharges (IEDs) to glucose levels 19 , we evaluated the extent to which IEDs were correlated to glucose levels in our dataset. In Subject 1 and Subject 3 with epilepsy, we found that IEDs in the seizure onset zone had lag-corrected correlation 0.22 and 0.20 with interstitial glucose variations, respectively (Supplementary Fig.…”
Section: Coupling Of Hypothalamic and Corticolimbic Activity To Perip...mentioning
confidence: 99%
See 1 more Smart Citation
“…1H, Paired t-test: all P < 0.05). As there have been studies associating interictal epileptiform discharges (IEDs) to glucose levels 19 , we evaluated the extent to which IEDs were correlated to glucose levels in our dataset. In Subject 1 and Subject 3 with epilepsy, we found that IEDs in the seizure onset zone had lag-corrected correlation 0.22 and 0.20 with interstitial glucose variations, respectively (Supplementary Fig.…”
Section: Coupling Of Hypothalamic and Corticolimbic Activity To Perip...mentioning
confidence: 99%
“…Thus, the HFA at any given point represents an average of one-minute recording. Similarly, the analytic signals of delta (1-4 Hz), theta (4-8 Hz), alpha (8)(9)(10)(11)(12), beta (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25), and gamma bands (25-70 Hz) were obtained using the same approach, except 4th order Butterworth filter was used as the bandpass filter. Interictal epileptiform discharges (IEDs) were computed using an automated algorithm as previously described 53 .…”
Section: Data Acquisition and Signal Preprocessingmentioning
confidence: 99%